Hydro-thermal regimes and their impact on relative weather disparities and grain yield of wheat in central Punjab - Bora, Sony; Kingra, P. K.; Pal, Raj Kumar (MAUSAM, 2025)
The temperature and humidity factors, known as Relative temperature disparity (RTD) and relative humidity disparity (RHD) along with phenology and crop yield were found to be significantly influenced by various sowing environments and irrigation regimes. RTD and RHD ranged between 47.71 to 64.65 and 34.68 to 63.07 respectively in Ludhiana, Punjab. The field experiment was conducted during the rabi season of 2021-22 and 2022-23 at Ludhiana (30.90° N, 75.85 °E and 247m above MSL) in split plot design with four replications with three dates of sowing ((D1= 27 October, D2= 17 November, D3= 8 December) and 3 irrigation regimes (I1= 4 irrigations at CRI, Jointing, 50% Flowering, Soft dough stages, I2= 3 irrigations at CRI, Flag leaf emergence, soft dough stage, I3= 2 irrigations at Jointing, Soft dough stage). The crop sown on 27 October took the maximum number of days to attain physiological maturity, followed by crop sown on 17 November and 8 December. Wheat sown on 17 November (4257.7 kg/ha) along with I1 irrigation level (4114.7 kg/ha) recorded the maximum yield. Higher RTD at vegetative stages (CRI, booting) and reproductive stage (milking) and lower RTD at maturity as well as higher RHD at booting and milking and lower at CRI and maturity resulted in higher yield in wheat sown on 17 November. With respect to timely sown crop, delay in sowing by 20 days resulted in decrease in the yield by 25.8 % while, advancement in sowing by 20 days indicated a decrement in the yield by 7.7 %.